Development of Android-Based Digital Modules for Learning Music History in the Era of the COVID-19 Pandemic - Pardomuan, Gusti Nyoman (Journal of World Science, 2022)
The current state of the COVID-19 pandemic has changed everything, one of which is in the education sector. Educational technology must also adapt to existing conditions. One of them is by developing digital modules for students to be able to carry out learning activities anywhere. The purpose of this research is to develop a learning media that is packaged in the form of an Android-based Digital Module for the History of Music course for second semester students of class A & B Department of Church Music at STAKPN Sentani which is one of the solution ideas to increase learning motivation and increase student learning experience towards digital learning resources. This research is a development research using the ADDIE model. The subjects in this study were content experts for the history of music, learning media experts, and individual student responses, small group students, and students in field trials on the products developed. The variables studied in this study are Android-based Digital Modules that are used during the current Covid 19 pandemic. Research data were collected using interview instruments and questionnaires. The research data were analyzed descriptively qualitatively, descriptively quantitatively, and inferential statistics (t-test). The results of the study indicate that a Digital Module has been successfully developed which is packaged in the form of Android for Distance Learning activities and has been valid for use. The results of the inferential statistical analysis of the t-test showed that the product developed was able to increase student learning motivation.